Veterans and Dependents of Spanish-American War : hearings before the United States House Committee on Veterans Affairs, Subcommittee on Spanish War, Eighty-Third Congress, second session, on Apr. 9, 1954. (U.S. Congressional Hearings., 1954)
Considers (83) H.R. 4667, (83) H.R. 5140, (83) H.R. 5143, (83) H.R. 5311, (83) H.R. 7112, (83) H.R. 7436, (83) H.R. 8721, (83) H.J. Res. 471, (83) H.J. Res. 477, (83) H.J. Res. 480, (83) H.J. Res. 490.